PRODIGE 59-DURIGAST trial: A randomised phase II study evaluating FOLFIRI + Durvalumab ± Tremelimumab in second-line of patients with advanced gastric cancer. Issue 4 (April 2021) - Evrard, Camille; Louvet, Christophe; Hajbi, Farid EL; Fiore, Frédéric DI; Malicot, Karine LE; Aparicio, Thomas; Bouché, Olivier; Laurent-Puig, Pierre; Bibeau, Frédéric; Lecomte, Thierry; Lièvre, Astrid; Guimbaud, Rosine; et al.
Abstract: Gastric or gastro-oesophageal junction (GEJ) adenocarcinomas present poor overall survival (OS). First-line chemotherapy regimen for patients with HER2-negative tumours is based on a doublet or triplet of fluoropyrimidine plus platinum salt ± taxane. Second-line chemotherapy (Docetaxel or Irinotecan) improves OS which nonetheless remains poor (around 5 months). The first results of immune checkpoint inhibitors (anti-PD-1) combined with chemotherapy in metastatic gastric and GEJ cancers were discordant in recent phase III trials. Data on dual-blockade (anti-PD-L1 or anti-PD-1 plus anti-CTLA-4) plus chemotherapy are lacking. DURIGAST is a randomised, multicenter, non-comparative, phase II study, evaluating safety and efficacy of FOLFIRI plus Durvalumab (anti-PD-L1) versus FOLFIRI plus Durvalumab and Tremelimumab (anti-CTLA-4) as second-line treatment of advanced gastric and GEJ adenocarcinoma. The primary objective is the rate of patients alive and without progression at 4 months. The main inclusion criteria are: patients with advanced gastric or GEJ adenocarcinoma, pre-treated with fluoropyrimidine + platinum salt ± taxane. Due to a lack of data on FOLFIRI, Durvalumab and Tremelimumab combination, a 2-step safety run-in phase has been performed before the randomised phase II. The safety run-in phase did not show any safety issue and the randomised phase II starts in September 2020.